Artikel Review : Bioaktivitas Bunga Rosella (Hibiscus sabdariffa L.) Beserta Pemanfaatannya - Karmana, I Wayan (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
Hibiscus sabdariffa is a species of the Malvaceae family which has long been used by humans as a traditional medicine. The use of Hibiscus sabdariffa as a traditional medicine is related to its bioactivity. Hibiscus sabdariffa has several pharmacological potentials, namely: 1) anticancer; 2) antioxidants; 3) antibacterial; 4) antiaging; 5) antiseptic; and 6) antihypertensive. The method of writing this article is a literature review published online, especially on Google Scholar using the keywords Hibiscus sabdariffa, bioactivity and utilization of Hibiscus sabdariffa. The results of this review state that rosella flowers (Hibiscus sabdariffa L.) have potential as anticancer, antioxidants, antihypertensive antibacterials, and low caffeinated tea drinks.